Detection of four foodborne pathogens based on magnetic separation multiplex PCR and capillary electrophoresis. Issue 1 (1st November 2021) - He, Shiyu; Huang, Yanzhi; Ma, Yingwei; Yu, Haoyan; Pang, Bo; Liu, Xingxing; Yin, Caihong; Wang, Xiaomu; Wei, Yuan; Tian, Yuling; Zhao, Chao; Xu, Kun; et al.
Abstract: Foodborne pathogen contamination is a major safety issue for many foods and is causing concern worldwide. In this study, a detection system based on magnetic separation, multiplex PCR (MPCR) and capillary electrophoresis (CE) technologies was developed for the simultaneous detection of four foodborne pathogens. Magnetic separation technology is used to rapidly capture pathogenic bacteria in food samples, and then a combination of MPCR and CE can be used to greatly increase detection sensitivity. The detection limit for bacterial DNA reached 10 −5 –10 −7 ng μL −1 and in the analysis of mocked food samples, the assay showed good sensitivity for bacterial detection ranging from 10 1 to 10 5 CFU mL −1 with excellent specificity. Compared to similar detection methodologies, this technique avoids the need for time‐consuming enrichment cultures, is more sensitive, and can be used to assay simultaneously four foodborne pathogens. Graphical Abstract and Lay Summary: Food‐borne bacteria contamination is one of the main problems of food safety, which seriously affects the economic development of many countries. In this study, the author achieved rapid separation and enrichment of multiple pathogens in a complex sample matrix through magnetic nano carbon dots, and constructed a rapid detection system for four foodborne pathogens by combining multiplex PCR and capillary electrophoresis technologies. This work shows great potential and application value in food safety monitoring.